PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA MATERI PERKALIAN BILANGAN CACAH SAMPAI 100 MELALUI PENERAPAN METODE CROSS LINE (GARIS) DI KELAS III SD NEGERI 1 SUMBER - Zaqiyatul Fakhiroh; Andi Ali Kisai; Hety Mariyanah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Mathematics learning in elementary school is essential for building a strong foundation of numeracy literacy, which helps learners understand mathematical concepts and solve everyday problems. Mastery of concepts from an early age, especially the material of multiplication of decimal numbers up to 100, is the foundation for the success of subsequent learning. However, at SD Negeri 1 Sumber, there are still students in grade III B who have difficulty understanding the concept of multiplication, especially stacked calculations. Classroom action research with a qualitative quantitative approach was conducted on 23 students of grade III B SD Negeri 1 Sumber in the 2024/2025 school year. The results showed a significant improvement in learning outcomes in each cycle: precycle averaged 24.78 (48% complete), cycle I averaged 47.83 (26% complete), and cycle II averaged 81.30 (78% complete) after the application of the cross line method. The highest value also increases from 90 to 100, and the lowest value from 0 to 50. This confirms the effectiveness of the cross line method in improving understanding of the concept and learning outcomes of multiplication of integers up to 100 independently.